2016
DOI: 10.1177/0894439316650163
|View full text |Cite
|
Sign up to set email alerts
|

Fast, Free, and Targeted

Abstract: Recruiting participants is a necessary step in many studies. With the advent of online research techniques, scientists are looking for new places where participants can be recruited online, in order to overcome the limitations of current sources and avoid the issues associated with sample overuse. The social media website “Reddit” is a potential source for recruitment, as it allows for free and rapid data collection from large samples, while enabling researchers to target specific populations when needed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(57 citation statements)
references
References 50 publications
0
57
0
Order By: Relevance
“…Data from January 2019 indicated that 1.65 billion people had used Reddit in the preceding 12 months [24]. Reddit may enable the targeting of more specific populations than Facebook [25]. To our knowledge, no studies have reported on the efficacy of Reddit as an online source for recruiting cancer survivors.…”
Section: Is Online Recruitment a Potential Solution?mentioning
confidence: 99%
“…Data from January 2019 indicated that 1.65 billion people had used Reddit in the preceding 12 months [24]. Reddit may enable the targeting of more specific populations than Facebook [25]. To our knowledge, no studies have reported on the efficacy of Reddit as an online source for recruiting cancer survivors.…”
Section: Is Online Recruitment a Potential Solution?mentioning
confidence: 99%
“…There currently exist few published articles where participants were recruited through Reddit to gauge reliably the quality of data collected through it. Using Reddit to recruit study participants is potentially advantageous for several reasons (Shatz 2017). First, it is possible to recruit large samples in a short amount of time.…”
Section: Scale Development and Subject Populationsmentioning
confidence: 99%
“…One such online forum is Reddit, with has been used with some success to recruit large samples quickly and at no cost. Reddit can also be used when researchers are interested in targeting specific groups (Shatz, 2017). One study suggests using seven guidelines for recruiting from Reddit specifically: post to a relevant subreddit; post to multiple relevant subreddits when necessary; clearly highlight the nature of the study in the post's title; post at an optimal time of day; note for demographics by time of time posting; keep surveys concise to avoid attrition; and engage with the community after posting if there are any questions (Shatz, 2017).…”
Section: Strategies For Recruiting Hard-to-reach Populationsmentioning
confidence: 99%